(untitled) (Jurnal Penelitian, 2010)
This research focuses on three fatwa of MUI that are regarded controversial, i.e. legal opinion on smoking, apolitical attitude, and under aged marriage. These three problems are viewed from maqâshid asy-syari’ah view. In legal opinion on smoking, maslahah that will be manifested is to avoid the negative effect of smoking. In this case, they used sad al-dzari’ah method. In legal opinion on apolitical attitude, they viewed that voters should vote their leader based on certain criteria. In this case they also used sad al-dzari’ah method. In legal opinion on under aged marriage, they tended to avoid under aged marriage practices to avoid madlarat, and, according to them, it is difficult to reach the objective of marriage. Under aged marriage, however, according to them, is still legal. To manifest this maslahah, they used maslahah al-mursalah, qiyas dan sadd adz-dzarî’ah altogether.